2020
DOI: 10.1101/2020.04.03.20052068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Validation of a Diagnostic Nomogram to Predict COVID-19 Pneumonia

Abstract: medRxiv preprint regression. This diagnostic nomogram was assessed by the internal and external validation data set. Further, we plotted decision curves and clinical impact curve to evaluate the clinical usefulness of this diagnostic nomogram. RESULTS:The predictive factors including the epidemiological history, wedgeshaped or fan-shaped lesion parallel to or near the pleura, bilateral lower lobes, ground glass opacities, crazy paving pattern and white blood cell (WBC) count were contained in the nomogram. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…To date, many studies have reported the detection of COVID-19 in patients suspected of infection. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 For instance, Menni et al. 16 reported the efficiency of self-reported symptoms in early identification of potential COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have reported the detection of COVID-19 in patients suspected of infection. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 For instance, Menni et al. 16 reported the efficiency of self-reported symptoms in early identification of potential COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…None of the BioRxiv posts were relevant to our topic. Of the 137 pre‐prints in MedRxiv, 23 nonduplicate studies included information on asthma, 29‐51 but none of them included specific information in children.…”
Section: Resultsmentioning
confidence: 99%
“…Other examples of approaches that use machine learning techniques for processing CT scan and X-Ray images can be found in [353] , [354] , [355] , [356] , [357] , [358] , [359] , [360] , [361] , [362] , [363] , [364] , [365] , [366] , [367] , [368] , [369] , [370] , [371] .…”
Section: Chest Computed Tomography and X-ray Image Processingmentioning
confidence: 99%